HYPER-SPECTRAL SHOOTING IN TERRITORY MANAGEMENT - Зацерковний, В. І. (Science-based technologies, 2015)
The following is investigated — basics physics of hyperspectral mapping (HSM) and the tasks that are being solved with their help. The efficiency of majority prioritized projects fulfilment in tasks of territory management is usually increasing when there is an implementation of modern geo-information systems, which are founded on getting the information from space. Behind the classification of object’s on aerospace pictures there are differences in their optic-spectral characteristics — spectral signatures. The more these objects differ from each other, and also from background surface (background), the easier it is possible to find them and the more precise is the result of classification. In order to differentiate the objects of different classes one should have details information about their spectral signatures, what is actually provided by HSM. Hyper-spectral data might be used both together with information about topology of inspected(observed) objects and separately. Essential growth of possibility to get useful information about target objects when using HSM is based on spectral differences of target objects and backgrounds. But the realization (implementation) of this approach is a serious problem predetermined by requirement to process huge scope of iconic (image) information (tens and hundreds of gigabytes) practically in real time scale. Modern hyper-spectrometers allow to get highly detailed spatial and spectral information about type and condition of natural and anthropogenic objects of Earth surface, and also about different dynamic processes that are happening on it, e.g. fires, droughts, etc.